The Relationship between interleukin 1beta and virulence factors produced by some bacteria isolated from patients with sinus infections - Shiamaa Al-Khazali; Suha Mahir; Mohanad Hasan (Tikrit Journal of Pure Science)
Background: Sinusitis is an inflammatory process of the mucosa lining the paranasal cavity. Currently, the term rhinosinusitis has been more accepted because rhinitis and sinusitis are continuous diseases. The study aimed to demonstrate the relationship between interleukin beta 1 and virulence factors of the bacteria that cause sinusitis. Method s::This study was conducted in Salah al-Din Governorate in the city of Balad in Balad General Hospital and Balad Healthcare Sector in the period from 1/11/2022 to 1/6/2023. From 1-50 years of both gender by taking nasal swabs with a carrier medium and blood samples, where 90 samples were collected from patients.Results: the present study showed that  Interleukin -beta 1.scored high sensitivity (91% and 83%) and specificity (84% and 60%) with significant differences (p<0.05) in screening patients with sinusitis, The positivity of Escherichia coli  13.3%  ,Staphylococcus haemolyticus 11.7%, Klebsiella pneumonia,  13.3%,Yersinia enterocolitica  8.3%,Providencia stuartii  8.3%, Staphylococeas epidermidi 18.3%, Pesedomonas oryzihabitans 15.0%, Leuconostoc psedomesenteroides 16.7%,and Burkhoderia cepacia 16.7% respectively .